2020
DOI: 10.3389/fonc.2020.568911
|View full text |Cite
|
Sign up to set email alerts
|

Germline Profiling and Molecular Characterization of Early Onset Metastatic Colorectal Cancer

Abstract: Background: Early onset colorectal cancer (EO CRC) is a heterogeneous colorectal cancer subtype with obvious hereditary tendencies and increasing incidence. We sought to determine the susceptibility genes and molecular characteristics of EO CRC. Methods: 330 EO metastatic CRC (mCRC) (≤55 years) and 110 average-onset (AO) mCRC patients (>55 years) were enrolled. Capture-based targeted sequencing was performed on tumor tissue and paired white blood cells using a sequencing panel of 520 genes. The association bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 35 publications
0
25
0
Order By: Relevance
“…Several studies have reported chemoresistance and anti-EGFR resistance in patients with SMAD4 -mutated mCRC ( 16 18 ), leading to poor prognosis. Furthermore, SMAD4 and RNF43 mutations were more commonly observed in early onset mCRC (≤55 years) ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported chemoresistance and anti-EGFR resistance in patients with SMAD4 -mutated mCRC ( 16 18 ), leading to poor prognosis. Furthermore, SMAD4 and RNF43 mutations were more commonly observed in early onset mCRC (≤55 years) ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have found that GSK3B deletion leaves HSCs in a precancerous state, and progression to acute myeloid leukaemia (AML) is facilitated after GSK3A deletion. 196 Although the mutation frequency of E3 ubiquitin ligase is lower than that of other WNT inhibitors, mutations of RNF43 (which mediates ubiquitin degradation of Frizzled) are still detected in the adenoma tissues of patients with GC, 218 early-onset metastatic CRC, 219 and Lynch syndrome. 220 RNF43 mutations are highly enriched in GC with microsatellite instability (MSI), promoting the development of GC cell resistance to DDR radiation and chemotherapy.…”
Section: Function Of the Wnt/β-catenin Pathway In Diseasesmentioning
confidence: 99%
“…Due to the importance of the HR pathway in cancer progression and drug resistance [ 43 ], the cancer relevance of FANC gene alterations at DNA and gene expression levels in various cancers has been considered. For example, germline mutations in FANCD2 , the representative of the FA pathway, are likely linked with the increased risk of metastatic CRC [ 44 ]. The overexpression of FANCD2 also predicts the increased probability of either lymph node metastasis or liver metastasis, which is reasonably associated with poor prognostic outcomes among CRC patients [ 45 ].…”
Section: The Fanconi Anemia Pathway In Dna Repair and Maintenance Of ...mentioning
confidence: 99%
“…As summarized in Table 1 , among 22 FANC genes, FANCS/BRCA1 and FANCD2/BRCA2 , high-risk hereditary breast-ovarian cancer syndrome susceptibility genes, are the most investigated as CRC susceptibility genes beyond its well-known predispositions [ 27 , 28 , 29 , 30 , 31 , 44 , 73 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 ]. Recent findings revealed that the prevalence of BRCA1/2 PVs among early-onset (1.3%) [ 30 ] and unselected patients with CRC (3.9%) [ 88 ] is more frequent than would be happening by chance.…”
Section: Potential Role Of Fanc Gene Mutations In ...mentioning
confidence: 99%